2023
DOI: 10.26434/chemrxiv-2023-mdm1x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deconstructing the potency and cell-line selectivity of membranolytic anticancer peptides

Abstract: Current cancer treatments damage healthy cells and tissues, causing short-term and long-term side effects. New treatments are desired that show greater selectivity toward cancer cells and evade the common mechanisms of multidrug resistance. Membranolytic anticancer peptides (mACPs) hold promise against cancer and multidrug resistance. The amphipathicity, hydrophobicity, and net charge of mACPs are all known to play a role in their respective interactions with cell membranes and the overall biological inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Draebing (2021) also found that aspect influences the thermal regime at the daily scale by producing diurnal temperature variations four times greater at southerly aspects compared to northerly aspects. In turn, the larger amplitude of warming-cooling cycles at south-facing aspects raises weathering rates both in the field and experimentally (Vasile and Vespremeanu-Stroe, 2016;Martínez-Martínez et al, 2023). The magnitude of minute-scale oscillations also increased at the Sydenham sites because changes in cloud cover and precipitation will result in more intense changes to rock surface temperature at southeastfacing aspects (Gunzburger et al, 2005;Fiorucci et al, 2020).…”
Section: Site-specific Factors Influencing Weathering Potentialmentioning
confidence: 98%
“…Draebing (2021) also found that aspect influences the thermal regime at the daily scale by producing diurnal temperature variations four times greater at southerly aspects compared to northerly aspects. In turn, the larger amplitude of warming-cooling cycles at south-facing aspects raises weathering rates both in the field and experimentally (Vasile and Vespremeanu-Stroe, 2016;Martínez-Martínez et al, 2023). The magnitude of minute-scale oscillations also increased at the Sydenham sites because changes in cloud cover and precipitation will result in more intense changes to rock surface temperature at southeastfacing aspects (Gunzburger et al, 2005;Fiorucci et al, 2020).…”
Section: Site-specific Factors Influencing Weathering Potentialmentioning
confidence: 98%